Enhanced Gain Characteristics of PbS-Doped Silica Fiber in O-Band by Co-Doping Er Ions - Xiuxiu Chen; Yanhua Dong; Jianxiang Wen; Hongyu Liu; Weizhu Ji; Xiangping Pan; Yanhua Luo; Tingyun Wang (IEEE Photonics Journal, 2023)
We report a novel PbS/Er co-doped silica fiber (PEDF) with improved spectral properties in O-band (1260–1360 nm). The results show that the gain of the PEDF exceeds 15 dB in the range of 1150–1360 nm. Compared to PbS-doped silica fiber, the PEDF has a gain improvement of 6.4–10.9 dB in O-band. In addition, the concentration of Pb and S in the PEDF core is significantly higher, and the size distribution of PbS nanoparticles is more concentrated in a narrow range. These factors may account for the enhanced gain characteristics of the PEDF. This work reveals the positive effect of co-doping Er3+ ions on the gain characteristics of the PEDF in O-band, and suggests an important research direction for the design of broadband amplifiers and light sources for optical communication with zero dispersion.